Diseño e implementación de un banco de pruebas electro neumático, para mejorar el aprendizaje de los estudiantes de la Universidad Politécnica Salesiana. - Andrade Espín, Álvaro Vinicio (2014)
This draft is based on an electro-pneumatic bench serve for practical circuits that allow the movement of pneumatic cylinders, pneumatic and electrical using pulsating, electric timers, limit switches and different types of valves and valve-elected. This project is aimed to research, consultancy and technological support within the National Plan for Good live as it will help the student and tutor to better understand the tires and electro-pneumatic systems. Within this document are the technical characteristics of pneumatic components, how to sizing the compressor, tank and system maintenance, also electrical components and a manual to work on Fluidsim software. Additional 10 practical format that can be performed on the bench where is the information for the teacher and the student is placed.